Explicating social values for resource allocation decisions on new cancer technologies: We, the jury, find⋯. (December 2017) - Stafinski, Tania; Menon, Devidas
Highlights: Multiple factors go into decision-making on resource allocation by the public. This is demonstrated with 2 Citizens' Juries in Alberta, Canada Choices made by the juries were almost completely the same, suggesting that findings from a single jury may be generalizable. Abstract: Aim of the study: To determine the general public's preferences in two communities to guide funding of cancer treatments. Methods: Two identical Citizens' Juries were conducted in the two major cities of Alberta, Canada. Two deliberative sessions were held with each jury, including small group and plenary sessions. The jurors participated in trade-off exercises, choosing between different populations of patients, which differed in up to 6 characteristics (number of patients; age; current health state; health outcome with treatment; prognosis without treatment; dependents). Forty-eight pairs of patient populations were generated using choice-based stated preference surveys. In addition, jury deliberations were analysed using qualitative methods Finally, the choices made by the 2 juries were compared using the Kappa statistic. Results: During the deliberations, the same arguments and issues were raised by both juries. The size of the patient population, its age and state of health without treatment, and the potential health gain with treatment all interacted when choices were being made by both juries. In general, there is a preference for treating those who are worst off or facing imminent death. There is also preference for younger populations over older ones, unless the older population is facing imminent death and can receive the same health gain as the younger population. Although, all things being equal, the preference is to treat a larger number of patients, it switches to the smaller group if the health gain to them is substantial. Finally, the two juries picked the same population in a choice pair in 47 of 48 cases. Conclusions: The public considers multiple factors simultaneously while making choices regarding resource allocation for cancer care. A single citizens' jury appears to be sufficient for eliciting views that are generalizable to a larger population.